Tax Literacy, Tax Sanctions, Taxpayer Awareness and Quality of Tax Services on Taxpayer Compliance in Payment of Land and Building Taxes in Dumai City (Riau) - Hidayat, Muhammad (Accounting Studies and Tax Journal (COUNT), 2024)
This research examines the influence of tax knowledge, tax sanctions, taxpayer awareness, and tax service quality on taxpayer compliance in paying land and building taxes. This research uses primary data with samples distributing questionnaires. The sampling  with a total of 97 questionnaires distributed. The dependent or dependent variable in this research is land and building tax compliance. The independent variables in this research are tax knowledge, tax sanctions, taxpayer awareness, and tax service quality. Testing this hypothesis uses multiple regression. The results of the research show that tax knowledge has no significant effect on taxpayer compliance, tax sanctions have no significant effect on taxpayer compliance, taxpayer awareness has no significant effect on taxpayer compliance, and tax service quality has no significant effect on mandatory compliance tax.